A non-natural nucleotide uses a specific pocket to selectively inhibit telomerase activity - Hernandez-Sanchez, Wilnelly; Huang, Wei; Plucinsky, Brian; Garcia-Vazquez, Nelson; Robinson, Nathaniel J.; Schiemann, William P.; Berdis, Anthony J.; Skordalakes, Emmanuel; Taylor, Derek J. (PLOS Biology, 2019)
Telomerase, a unique reverse transcriptase that specifically extends the ends of linear chromosomes, is up-regulated in the vast majority of cancer cells. Here, we show that an indole nucleotide analog, 5-methylcarboxyl-indolyl-2′-deoxyriboside 5′-triphosphate (5-MeCITP), functions as an inhibitor of telomerase activity. The crystal structure of 5-MeCITP bound to the Tribolium castaneum telomerase reverse transcriptase reveals an atypical interaction, in which the nucleobase is flipped in the active site. In this orientation, the methoxy group of 5-MeCITP extends out of the canonical active site to interact with a telomerase-specific hydrophobic pocket formed by motifs 1 and 2 in the fingers domain and T-motif in the RNA-binding domain of the telomerase reverse transcriptase. In vitro data show that 5-MeCITP inhibits telomerase with a similar potency as the clinically administered nucleoside analog reverse transcriptase inhibitor azidothymidine (AZT). In addition, cell-based studies show that treatment with the cell-permeable nucleoside counterpart of 5-MeCITP leads to telomere shortening in telomerase-positive cancer cells, while resulting in significantly lower cytotoxic effects in telomerase-negative cell lines when compared with AZT treatment.